Co-Pyrolysis Characteristics of Indonesia Low Rank Coal and Oil Palm Empty Fruit Bunch - Siti Zullaikah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Co-pyrolysis behaviors of Indonesia low rank coal and oil palm empty fruit bunch were studied in a droptubed reactor under nitrogen atmosphere. The pyrolysis temperatures were 300 oC, 400 oC, 500 oC, 600 oC and 700 oC, respectively. Five differents biomass ratios (coal/oil palm empthy fruit bunch (w/w): 100/0, 75/25, 50/50, 25/75, 0/100) were used. Gas and tar components were analyzed by a gas chromatograph and a gas chromatography–mass spectrometry, respectively. Under co-pyrolysis conditions, the gas volume yields are lower than the calculated values and H2 content in the gas phase was higher. The changes of gas yield and components are probably caused by the secondary reactions and tar decomposition.Co-pyrolysis tar contains more acid and ester compounds. The addition of biomass changes the atmosphere during the pyrolysis process and promotes tar decomposition. The results of char yields were higher than the calculated values during co-pyrolysis.